PENGEMBANGAN MULTIMEDIA BERBASIS KEARIFAN LOKAL TERINTEGRASI PROFIL PELAJAR PANCASILA PADA MATA PELAJARAN IPAS MATERI ENERGI KELAS IV DI SDN KLIWONAN - Wahyu Eka Febrianti; Nur Ngazizah; Muflikhul Khaq (Jurnal Binagogik, 2024)
The problem of this research is based on problems, namely that the learning media has not been varied, the multimedia used is not in accordance with the needs of students, local wisdom and the Pancasila student profile have not been applied in learning activities. This research aims to: 1) Produce a product in the form of multimedia based on local wisdom integrated with Pancasila student profiles in the science and energy subject class IV at SDN Kliwonan. 2) Knowing the feasibility of the learning multimedia being developed. This research is Research and Development (R&D) research using the 4D model (Define, Design, Development and Dissementation). This research was carried out in class IV of Kliwonan State Elementary School, totaling 30 students. The data collection techniques used are observation, interviews, questionnaires, documentation and tests. The instruments used were validation questionnaires for material experts, media experts, teachers, student responses, learning implementation observation sheets, Pancasila student profile attitude observation sheets and One Group Pretest and Posttest questions. The research results showed that: 1) A multimedia product based on local wisdom integrated with student profiles was produced. Pancasila, science and technology subject, class IV energy material at SDN Kliwonan with the 4D model 2) The feasibility of multimedia in the validity aspect gets a percentage of material experts of 93.3% in the very valid category, media experts in the valid category 84.09%, and teachers in the 95.1% category. very valid. The practicality aspect of multimedia from assessing students' responses in limited trials was 95%, extensive trials were 94%. The learning implementation results from observer I were 96.8% and observer II was 95.3%. Judging from the percentage of student response results and the multimedia learning implementation sheet, the criteria are very practical. The effectiveness aspect is based on a comparison of students' pretest and posttest scores, with a Gain Score of 0.7 in the effective category. The results of the assessment of the Pancasia student profile attitude observation sheet in the six aspects were >2.50 in the very effective category. Based on the results above, multimedia is declared feasible.